2007
DOI: 10.1039/b707121c
|View full text |Cite
|
Sign up to set email alerts
|

Bioreductive activation and drug chaperoning in cobalt pharmaceuticals

Abstract: The potential for cobalt(III) complexes in medicine, as chaperones of bioactive ligands, and to target tumours through bioreductive activation, has been examined over the past 20 years. Despite this, chemical properties such as reduction potential and carrier ligands required for optimal tumour targeting and drug delivery have not been optimised. Here we review the chemistry of cobalt(III) drug design, and recent developments in the understanding of the cellular fate of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(119 citation statements)
references
References 68 publications
1
111
0
2
Order By: Relevance
“…[77] Other Anti-Cancer Agents XANES analysis of intracellular cobalt has been important for the development of cobalt complexes as potential hypoxia-activated prodrugs. [78][79][80] The concept was to exploit the hypoxic nature of tumours whereby the inert Co(III) complexes could be reduced to the labile Co(II) complexes in the reducing environment, and subsequently release an active anti-cancer agent. [78][79][80] The XANES studies involved the systematic study of a mixture of Co(III) and Co(II) complexes to differentiate between the oxidation states.…”
Section: Arsenic-containing Anti-cancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[77] Other Anti-Cancer Agents XANES analysis of intracellular cobalt has been important for the development of cobalt complexes as potential hypoxia-activated prodrugs. [78][79][80] The concept was to exploit the hypoxic nature of tumours whereby the inert Co(III) complexes could be reduced to the labile Co(II) complexes in the reducing environment, and subsequently release an active anti-cancer agent. [78][79][80] The XANES studies involved the systematic study of a mixture of Co(III) and Co(II) complexes to differentiate between the oxidation states.…”
Section: Arsenic-containing Anti-cancer Agentsmentioning
confidence: 99%
“…[78][79][80] The concept was to exploit the hypoxic nature of tumours whereby the inert Co(III) complexes could be reduced to the labile Co(II) complexes in the reducing environment, and subsequently release an active anti-cancer agent. [78][79][80] The XANES studies involved the systematic study of a mixture of Co(III) and Co(II) complexes to differentiate between the oxidation states. [78] It was noted that the analysis of Co in cells was complicated by changes in the coordination sphere of Co(III) complexes, and that XANES was useful for monitoring the oxidation state as long as the ligand exchange reactions of Co(III) were slow relative to the reduction to Co(II).…”
Section: Arsenic-containing Anti-cancer Agentsmentioning
confidence: 99%
“…[15][16][17] Im Komplex [18][19][20] sowie die Bildung kovalenter Bindungen durch photochemische [21,22] (oder weniger spezifische) [23,24] [28,29] Außerdem werden Komplexe von bioaktiven Liganden mit substitutionsinerten Metallen als Prodrug eingesetzt, die erst nach dem Eindringen in die Zelle aktiviert werden. [30,31] Wegen der sehr langsamen Bildung der Co 3+ -Komplexe wird eine indirekte Präparation bevorzugt, wobei erst der Komplex mit dem substitutionslabilen zweiwertigen Ion gebildet und an- …”
unclassified
“…16 The bite angle of phen (N5-Co1-N6 angle) is 74.69 (18) , whereas for the hydrazone ligand, the bite angles vary between 75.63(16) and 76.70 (13) . The distortion, from a regular octahedral geometry is evident from the N2-Co1-N4 trans-bond angle value of 162.49 (17) , while the other two trans angles, O1-Co1-N6 and O2-Co1-N5 are 164.32(17) and 168.22 (14) , respectively. When compared the corresponding bond lengths of the Ni(II) complex with that of the Co(II) complex, it was found that the distances of Ni-N and Ni-O are both shorter than the corresponding Co-N and Co-O bond distances.…”
mentioning
confidence: 99%